The Importance of Siren in Greening - Sharifboyevich, Kurbanov Ibragimjon (American Journal of Biology and Natural Sciences, 2025)
This article discusses the Siren plant, widely used in landscape construction and landscape architecture, as well as in landscaping of residential areas. The main objective of the study is to study the methods of selection of Siren, resistant to any climatic conditions and possessing high decorative qualities.